Survei Kemampuan Teknik Dasar Passing Bawah Ekstrakurikuler Bolavoli - Prayogatama, Bagus (Universitas Negeri Malang, 2021)
Abstract: This study aims to determine the basic technical skills of passing under by using tests on extracurricular participants at SMP Negeri 5 Jombang. This study uses descriptive quantitative data analysis with survey research methods. The research subjects were volleyball extracurricular members at SMP Negeri 5 Jombang which consisted of 18 students. Based on the results of the study, the results of the data analysis on the basic skills of passing under volleyball for the male extracurricular participants were in the moderate category and for the process assessment was included in the sufficient category, while the female volleyball extracurricular participants were in the sufficient category for the outcome assessment and process assessment. So there is 25% good, 25% good enough and 50% good enough.Â Abstrak: Penelitian ini menggunakan analisis data deskriptif kuantitatif dengan metode penelitian survey. Subjek penelitian adalah peserta ekstrakurikuler bolavoli SMP Negeri 5 Jombang yang terdiri dari 18 siswa. Berdasarkan hasil penelitian bahwa hasil analisis data tes keterampilan dasar passing bawah bolavoli peserta ekstrakurikuler putra masuk dalam kategori sedang dan untuk penilaian proses termasuk dalam kategori cukup sedangkan peserta ekstrakurikuler bolavoli putri termasuk dalam kategori cukup untuk penilaian hasil dan penilaian proses. Jadi ada 25% baik, 25% cukup dan 50% cukup.